Correlation of precancerous lesion incidence with duodenogastric reflux and N-nitroso compound duration at reflux and antireflux stomach surgery – An experimental study - Zlatić, Aleksandar; Marinković, Mirjana; Mihailović, Dragan; Radojković, Milan; Dinić-Radovanović, Biljana; Djordjević, Miodrag; Korica, Milan; Veljković, Radovan (Vojnosanitetski pregled, 2020)
Background/Aim. Duodenogastric reflux occurs after gastroenteroanastomosis, with or without resection of the stomach (Billroth I, Billroth II), after vagotomy and pyloroplasty, gastroduodenostomy as well as in conservatively treated patients. The aim of this study was to analyse the effect of carcinogenic N-nitroso compounds (MNNG) influence in conjunction with duodenogastric reflux, in the function of time for precancerous lesions development in gastric mucosa. A particular purpose of the study has been to suggest some effective surgical procedures, which could prevent the harmful effects of duodenogastric reflux on gastric mucosa, as a potential activator of carcinogenesis. Methods. The research included 90 experimental, male Wistar rats, divided into 3 groups. The two experimental groups were subjected to two surgical procedures: Billroth II gastric resection (group B2), and the Roux-en-Y reconstruction (group RY), respectively. The control group (group C) animals did not receive any surgical treatment. All groups were administered per os chemical cancerogen MNNG. All anastomoses were performed by extra mucosal suture with monofilament polypropilene 7–0, and 8–0. The animals were sacrificed consecutively, and subjected to total gastrectomy after 8, 16 and 24 weeks. Results. Pathohistological analysis was performed on defined regions of the rat stomach in three time period. The B2 group, at the end of our experiment, showed predominant incidence of severe lesions: hyperplasia (0%), gastritis (0%), metaplasia (6.7%), dysplasia (46.7%), early carcinoma (20%) and carcinoma (26.7%). At the end of our experiment, the RY and C groups showed the similarities of the obtained results related to time with predominant incidence of mild lesions: hyperplasia (13.3% vs 0%, respectively), gastritis (13.3% vs 13.3%, respectively), metaplasia (6.7% vs 13.3%, respectively), dysplasia (66.7% vs 66.7%, respectively), with an extremely low incidence of early carcinoma (0% vs 6.7%, respectively) and no incidence of carcinoma (0% vs 0%, respectively). Conclusion. Without the presence of duodenogastric reflux, MNNG causes a low degree of precancerous gastric lesions. However, direct contacts of MNNG with gastric mucosa, including the presence of duodenogastric reflux, induce precancerous lesions and carcinoma. The percentage of reversible changes decreases with time, while the percentage of irreversible lesions and carcinoma increases. A lack of distinction in the findings between the RY and C groups confirms a gastroprotective role of the Roux-en-Y procedure.
Keywords: duodenogastric reflux; gastric mucosa; precancerous condi¬tions; stomach neoplasms; nitroso compounds; digestive system surgical procedures; disease model, animal; rats.